2022
DOI: 10.3390/antibiotics11101340
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Phage Therapy: A Systematic Review of Clinical and Safety Trials

Abstract: Trials of phage therapy have not consistently reported efficacy. This contrasts with promising efficacy rates from a sizeable and compelling body of observational literature. This systematic review explores the reasons why many phage trials have not demonstrated efficacy. Four electronic databases were systematically searched for safety and/or efficacy trials of phage therapy. Sixteen trials of phage therapy were included, in which 378 patients received phage. These were divided into historical (pre-2000; N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 60 publications
(120 reference statements)
0
24
0
Order By: Relevance
“…However, there is an explainable discrepancy between the efficacy of phage therapy reported by observational and clinical trial data. This is because it is difficult for trials to consistently achieve the “goldilocks constellation” of getting a sufficient quantity of phages with the correct specificity to the site of infection; an in-depth exploration of trial data has been published elsewhere [ 37 ]. Nevertheless, the Antibiotic Resistance Leadership Group in the United States and Healthcare Improvement Scotland have concluded that there is sufficient evidence to consider phage therapy as a treatment option in patients with difficult-to-treat infections [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an explainable discrepancy between the efficacy of phage therapy reported by observational and clinical trial data. This is because it is difficult for trials to consistently achieve the “goldilocks constellation” of getting a sufficient quantity of phages with the correct specificity to the site of infection; an in-depth exploration of trial data has been published elsewhere [ 37 ]. Nevertheless, the Antibiotic Resistance Leadership Group in the United States and Healthcare Improvement Scotland have concluded that there is sufficient evidence to consider phage therapy as a treatment option in patients with difficult-to-treat infections [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of phage therapy as an unlicensed medicine is underpinned by a sizeable body of reassuring evidence about the safety and efficacy of phage therapy. For example, there have been 13 safety or clinical trials of phages since the year 2000, all of which have shown phages to be safe by a variety of routes of administration [ 9 ]. Meanwhile, there have been >2200 clinical reports of phage since the year 2000, among which 79% of 1904 patients showed clinical improvement and 87% of 1461 patients achieved bacterial eradication; many of these cases were refractory to antibiotic therapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there have been >2200 clinical reports of phage since the year 2000, among which 79% of 1904 patients showed clinical improvement and 87% of 1461 patients achieved bacterial eradication; many of these cases were refractory to antibiotic therapy [ 10 ]. Clinical trials meanwhile have not consistently demonstrated efficacy, although this is considered to arise from shortcomings in the trials themselves and not to reflect the mechanistic ability of lytic phages to infect and kill their bacterial hosts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages ('phages') offer an alternative antibacterial strategy to conventional antimicrobial drugs and may be of enhanced value in the current antimicrobial drug-resistant era (44)(45)(46)(47)(48). They may be useful in combination with existing antibacterial agents (46,49).…”
Section: Introductionmentioning
confidence: 99%